La colonna senza fine . The Endless Column - Mereghetti, Elisa (Ethnos ; Vag61 ; Occhiobago, 2008)
Verzio FF Submission “The Endless Column” tells the story of the Roma community that has been living in Bologna, Italy, since 2002. The film makes use of footage by independent video makers, images by several photographers and information provided by Bolognese activists. The Roma people, originally from Craiova, Romania, have walked the streets of Bologna since the end of the 90s, but the city notices their presence only in September 2002, when they are forcibly evicted from their poor shacks along the banks of the River Reno. In via Casarini, the International Migrant Station is occupied and made available to the Roma community. A series of collective events and individual stories are presented in this film. 5 years after the first eviction some of the Roma people have found apartments and jobs, but the majority continue to live like ghosts, in an endless escape, chased by bulldozers and police roundups.